Bernard Malamud’s Fictional Forte in Tending the Resources of Human Personality for Effecting Human Relationship through Suffering in His Fictional World: An Appraisal: Exploring the Dynamics of Human Relationships and Moral Responsibility in Bernard Malamud's Fictional World (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper throws light on the human potential for effecting human relationship and suffering as depicted in Bernard Malamud’s fictional world which shows how his imagination is undoubtedly proof of human relationships and moral responsibility. The only alternative to curb the evils of the society is eating away such evils at all levels. The complete application of his theme won him an important place in the twentieth century American fiction.